Autonomía universitaria y libertad de cátedra en tiempos de cambio - Campos-Céspedes, Jensy; Solano Gutiérrez, Walter (Innovaciones Educativas, 2020)
This paper offered some basics elements related to university autonomy and academic freedom, with the aim of promoting reflection around these two concepts, which, for some, turn out to be elusive and controversial, especially in the new educational contexts in which Planetary changes change the actions of the universities and their teaching activities. A synopsis of the historical evolution of the university and a discussion on the concepts of university autonomy and academic freedom are offered, in light of its necessary reconceptualization in current societies, characterized by the obsolescence of knowledge and the deconfiguration of the great stories that structured the speeches and tasks of the university institutions of yesteryear. in light of their necessary reconceptualization in current societies, characterized by the obsolescence of knowledge and the deconfiguration of the great stories that structured the discourses and tasks of the university institutions of yesteryear. Virtualization, the emergence of the figure of prosumers and the development of information and communication technologies, among other advances, demand a reconfiguration of university institutions in terms of what has traditionally been conceived as academic freedom and university autonomy.